Aretha Franklin : Lady Soul - Gourse, Leslie (New York : F. Watts, 1995)
Explores Aretha Franklin's life and musical development, from her childhood in Detroit to her continued success in the recording industry.
Includes bibliographical references (p. 155) and index.
Includes discography (p. 153-154) and videography (p. 155).
Wilson's Senior High School.
Young Adult
Keywords: Franklin, Aretha -- Juvenile literature; Franklin, Aretha; Franklin, Aretha; Soul musicians -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Singers; Soul music; Women -- Biography; African Americans -- Biography; Singers -- Biography; Soul musicians -- Biography; Women -- Biography